Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.5194/we-9-8-2009
|View full text |Cite
|
Sign up to set email alerts
|

The shape of occupancy distributions in plant communities: the importance of artefactual effects

Abstract: Occupancy frequency distributions are commonly used as an approach to describe and analyse interspecific distribution patterns. However, the relative importance of biological versus artefactual mechanisms in shaping occupancy distributions is still largely undetermined. We evaluated the importance of different and interacting artefactual effects on the shape of occupancy distributions in local plant communities. The effects of sampling protocol parameters (i.e. size and number of sample units, sample extent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Several previous studies (e.g., Franzén & Eriksson, 2001;Leite & Lopes, 2001;Perelman et al, 2001) also revealed the overwhelming prevalence of satellite over core species, resulting in unimodal distributions at metacommunity level. Moreover, some authors have suggested that the core mode (bimodality) emerges as a consequence of the statistical properties of species occupancy probability distributions (Hui & McGeoch, 2007) or a pure artefact of the sampling protocol (Kammer & Vonlanten, 2009). With an increasing fraction of ruderal species and canopy openness, the slopes of RSOC's head became milder and eventually, in ruderal herbaceous communities, these curves are expected to form a 'shoulder' and approach a sigmoidal shape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies (e.g., Franzén & Eriksson, 2001;Leite & Lopes, 2001;Perelman et al, 2001) also revealed the overwhelming prevalence of satellite over core species, resulting in unimodal distributions at metacommunity level. Moreover, some authors have suggested that the core mode (bimodality) emerges as a consequence of the statistical properties of species occupancy probability distributions (Hui & McGeoch, 2007) or a pure artefact of the sampling protocol (Kammer & Vonlanten, 2009). With an increasing fraction of ruderal species and canopy openness, the slopes of RSOC's head became milder and eventually, in ruderal herbaceous communities, these curves are expected to form a 'shoulder' and approach a sigmoidal shape.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of the relative importance of each of these factors is further complicated by their confounding effects as well as by sampling artefacts. Indeed, the form of OFDs has been demonstrated to be scale-dependent (Collins & Glenn, 1997;van Rensburg et al, 2000;Kammer & Vonlanten, 2009). For instance, the inflation of the satellite mode at higher scale levels may be due to the low detection rates of rare species whose frequencies are underestimated (Nee et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these factors could modify the occupancy of the species through an increasing proportion of satellite or core species. Obviously, the observed OFD pattern reflects the interplay of these factors and is also influenced by sampling parameters (Heatherly et al., 2007 ; see Table 5 in Kammer & Vonlanthen, 2009 ). It follows that the individual contribution of each factor to OFD pattern is rather complicated to explore (Gafta et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins [ 10 ] built on the intermediate disturbance hypothesis [ 18 ] and studies of species occupancy [ 19 - 22 ] to develop hypotheses for RSOC shapes, suggesting those shapes should vary along a successional gradient, and as a result, on a spatial gradient in disturbance. He suggested that with high disturbance, recruitment limitation should cause an exponential RSOC where some disturbance-adapted species are prevalent but most others rare.…”
Section: Introductionmentioning
confidence: 99%